Corrigendum: Follow-up of young adult monozygotic twins after simultaneous critical coronavirus disease 2019: a case report (Frontiers in Medicine, (2022), 9, (1008585), 10.3389/fmed.2022.1008585) - de Castro, Mateus V. (2023)
In the published article, there was an error in the author list, and author Giuliana X. de Medeiros was erroneously excluded. The corrected author list appears below. Mateus V. de Castro1†, Monize V. R. Silva1†, Flávia B. Soares1, 2†, Vivian R. Cória1, Michel S. Naslavsky1, 2, Marilia O. Scliar1, 2, Erick C. Castelli3, Jamile R. de Oliveira4, 5, Giuliana X. de Medeiros4, 5, Greyce L. Sasahara5, Keity S. Santos4, 5, 6, Edecio Cunha-Neto4, 5, 6, Jorge Kalil4, 5, 6 and Mayana Zatz1, 2* The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.